Gate dielectric material dependence of current-voltage characteristics of ballistic Schottky barrier graphene nanoribbon field-effect transistor and carbon nanotube field-effect transistor for different channel lengths - Ahmed, Sheikh Ziauddin; Shawkat, Mashiyat Sumaiya; Chowdhury, Md Iramul Hoque (© 2015 The Institution of Engineering and Technology., 2016)
This article was published in Micro and Nano Letters [© 2015 Published by The Institution of Engineering and Technology] and the definite version is available at: http://doi.org/10.1049/mnl.2015.0193